Mahaga: Peran Strategis Lembaga Perempuan Dayak (LPD) Provinsi Kalimantan Tengah dalam Pendidikan Masyarakat melalui Pelestarian Produk Budaya - Pratiwi, Endah Yusma; Mardiana; Ferudyn, Ade Yusuf; Girindraswari, Nawung Asmoro; Tuti Nababan, Cani Crihas; Latifah, Nurul (Global Action and Education for Society, 2026)
The background of this study lies in the importance of women’s roles in preserving and transmitting Dayak cultural values amidst rapid social change. The aim of this research is to describe the role of the Dayak Women’s Institution of Central Kalimantan Province (LPD Kalteng) in community education through cultural preservation, to identify the challenges faced, and to explain the strategies employed to overcome those challenges. This study uses a qualitative approach with data collected through interviews, observation, and documentation. The research informants consist of the institution’s administrators and members. Data were analyzed through the processes of reduction, presentation, and conclusion drawing. The findings reveal that LPD Kalteng functions as a cultural education agent, bridging the preservation of traditional values with the needs of contemporary society. This role is reflected in various educational and cultural activities such as traditional costume seminars, cultural product bazaars, training in local product development, the use of YouTube as an educational medium, and the habituation of the Manasai dance in every event. The main obstacles faced include limited financial resources, low member participation due to time constraints, program self-reliance, and a lack of content production tools. To address these challenges, the institution implements strategies such as strengthening internal solidarity, optimizing leadership roles, and expanding external collaborations. The study concludes that, despite existing limitations, LPD Kalteng successfully plays a significant role in preserving cultural heritage while simultaneously educating the community.